The Development of Learning Achievement in Military Theory Course Through Integrated Learning Activities of the Sophomore at Guang Zhon Huashang Vocational College - Deng, Xiaopian; Boontongtherng, Poosit (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aims: In the current educational environment, military theory classes have always been regarded as a special learning experience. Guangzhou Huashang Vocational College offers military theory courses for sophomore students, aiming to improve students’ military accomplishment and national defense awareness through systematic theoretical study and practical operation. However, there are several issues concerning the setting and implementation of this curriculum that are worth exploring in depth. For example, does military theory have an impact on the academic success of sophomore students? Is the effect positive or negative? How satisfied are students with the course? Based on the concern of these problems, this study takes the sophomore students of Guangzhou Huashang Vocational College as the research object, analyzes the teaching practice of military theory courses, and discusses the influence of military theory courses on academic achievement. The objectives of this research were 1) To compare academic achievement in Development of Learning Military Theory Course subjects before and after the blended learning. 2) Study on students’ satisfaction towards integrated learning activities. 3) Study students’ interest in interactive games in integrated learning activities. Methodology: The research tools include 1) A blended by traditional learning management plans, a total of 6 plans. 2) Academic achievement with multiple choice test before class - after class total of 30 items.3) A questionnaire on students’ satisfaction towards integrated learning activities totals 10 items.4）A questionnaire on students’ interest in interactive games in integrated learning activities totals 5 items. Results: The results of the research found that 1) Academic achievement after the blended learning arrangement was higher than before with statistical significance at the.05 level.2) Students were satisfied with the integrated teaching and learning arrangement. at a high level 3) Students’ interest in interactive games in integrated learning activities at a high. Conclusion: The study discovered that the use of blended learning greatly increased academic achievement and that students expressed great satisfaction with both the integrated teaching strategy and the interactive games incorporated into the learning activities.